Process for Growth of Group-IV Alloys Containing Tin by Remote Plasma Enhanced Chemical Vapor Deposition - Claflin, B.; Grzybowski, G. J.; Ware, M. E.; Zollner, S.; Kiefer, A. M. (Frontiers in Materials, 2020)
A remote plasma enhanced chemical vapor deposition process using GeH4, SiH4 and SnCl4 precursors has been developed for epitaxial growth of group-IV alloys directly on Si (001) substrates, without the need for buffer layers. X-ray diffraction measurements of a representative Ge1-xSnx sample which is 233 nm thick, with x = 9.6% show it to be highly oriented along the [001] direction and nearly relaxed, with 0.37% compressive strain. Ellipsometry measurements provide a pseudo-dielectric function which is well fitted by a 3-layer (substrate/alloy/surface oxide) model. Cross-sectional transmission-electron-microscope images show a highly defective interface layer, ~ 60 nm thick, containing edge dislocations and stacking faults; above this layer, the lattice is well-ordered, with a much lower density of defects. Atomic force microscopy measurements show an RMS roughness of 1.2 nm for this film.